High-frequency supercapacitors surpassing dynamic limit of electrical double layer effects - Zhangshanhao Li; Minghao Xu; Yier Xia; Ziyun Yan; Jianyou Dai; Bingmeng Hu; Haizhao Feng; Sixing Xu; Xiaohong Wang (Nature Communications)
Abstract The prosperity of microelectronics has intensified the requirement for miniaturized power systems using capacitors with high capacity and broad frequency ranges. Electrochemical supercapacitors stand out with their superior capacitance density, surpassing traditional electrolytic capacitors by at least two orders of magnitude. However, the intrinsic slow ion dynamics of electrical double layer effects greatly limit supercapacitors characteristic frequency, constraining their applicability in microsystems. This work constructs a near-ideal micro electrochemical supercapacitor, featuring the monolayer graphene as a working electrode, to reveal the ceiling of electrochemical capacitance characteristic frequency. To address this limitation, we introduce a Hybrid Electrochemical Electrolytic Capacitor design, which asymmetrically coupling the electrochemical and dielectric effects. At low frequencies, the electrochemical segment provides sufficient capacity, while its electrolytic segment takes over at high frequencies, broadening the frequency range. Consequently, the hybrid design boasts considerable capacitance density across a broad frequency range. Employing our wafer-scale microfabrication techniques, we showcase a device, achieving a characteristic frequency of 44 kHz and a volume capacitance density of 800 $${{\rm{μ }}}{{\rm{F}}}/{{{\rm{cm}}}}^{3}$$ μ F / cm 3 . To demonstrate its practicality in microsystems, the device is integrated with a power management chip and buck circuit module, respectively, with only 2 % space usage compared to commercial electrolytic capacitor, achieving the same performance.